Injectable exosome-functionalized extracellular matrix hydrogel for metabolism balance and pyroptosis regulation in intervertebral disc degeneration - Xing, Hongyuan; Zhang, Zengjie; Mao, Qijiang; Wang, Chenggui; Zhou, Youlong; Zhou, Xiaopeng; Ying, Liwei; Xu, Haibin; Hu, Shaojun; Zhang, Ning (Journal of nanobiotechnology, 2021)
Exosome therapy is a promising therapeutic approach for intervertebral disc degeneration (IVDD) and achieves its therapeutic effects by regulating metabolic disorders, the microenvironment and cell homeostasis with the sustained release of microRNAs, proteins, and transcription factors. However, the rapid clearance and disruption of exosomes are the two major challenges for the application of exosome therapy in IVDD. Herein, a thermosensitive acellular extracellular matrix (ECM) hydrogel coupled with adipose-derived mesenchymal stem cell (ADSC) exosomes (dECM@exo) that inherits the superior properties of nucleus pulposus tissue and ADSCs was fabricated to ameliorate IVDD. This thermosensitive dECM@exo hydrogel system can provide not only in situ gelation to replenish ECM leakage in nucleus pulposus cells (NPCs) but also an environment for the growth of NPCs. In addition, sustained release of ADSC-derived exosomes from this system regulates matrix synthesis and degradation by regulating matrix metalloproteinases (MMPs) and inhibits pyroptosis by mitigating the inflammatory response in vitro. Animal results demonstrated that the dECM@exo hydrogel system maintained early IVD microenvironment homeostasis and ameliorated IVDD. This functional system can serve as a powerful platform for IVD drug delivery and biotherapy and an alternative therapy for IVDD.